McMaster Health Forum: Towards a Canadian Response to Emerging Global Health Issues - AlKhatib, Ahmad H.; Tang, Theresa (The Meducator, 2012)
Health is now truly global. Health crises in one part of the world can affect the health of people everywhere. Governments around the world are increasingly recognizing the importance of acting upon global health issues as a means of protecting national health security. They have begun to invest in the necessary governmental infrastruc-ture and domestic partnerships needed to coordinate a national response to address global health issues. Norway, Switzerland and the United Kingdom, among others, have now developed national global health strategies that ar-ticulate national global health objectives and the means by which government agencies and departments can co-operate towards achieving them. Canada has not yet developed anything similar; its e!orts to address global health issues remain largely uncoordinated and reactive. Ahmad AlKhatib and Theresa Tang, McMaster Health Fo-rum Fellows (2010-11), discuss the Forum’s planned stakeholder dialogue on “health and emerging global issues” – a key first step in the development of an evidence-informed Canadian response to emerging global health issues.